Acute and subacute toxicity evaluation of hydroalcoholic extract of Caryota urens leaves in Wistar rats - Sujitha Balaji, Kripa Kavasseri Ganesan (Journal of Applied Pharmaceutical Science, 2020)
Caryota urens native to Srilanka and India grows in tropical and subtropical regions. It is rich in nutrition and show pharmacological properties owing to the presence of flavonoids, coumarins, carbohydrates, and amino acids. However, scientific reports which guarantee the safety of C. urens are not available. Therefore, the intention of the current investigation was to assess the potential toxicity of the hydroalcoholic extract of C. urens leaves (CULHA) in Wistar rats. In acute toxicity study, CULHA was administered at a single oral dose of 2,000 mg/kg body weight. In subacute toxicity study, CULHA was administered once a day at three dose levels of 100, 200, and 400 mg/ kg body weight for 28 days. At the end of the treatment, animals were sacrificed; vital organs were removed and examined histopathologically. Blood and serum samples were collected and processed immediately for the analysis of hematological and biochemical parameters. During acute toxicity study, treatment-associated death or manifestation of toxic clinical symptoms were not seen. Furthermore, results of both acute and subacute toxicity group exposed to CULHA did not exhibit significant change in hematology, biochemical parameters, and histopathology. The results demonstrated that CULHA did not possess potential to induce toxicity.
Keywords: Caryota urens, acute toxicity, subacute toxicity, Wistar rats, herbal medicine.